VICTIMS OF THE AGRICULTURAL COLLECTIVIZATION POLICY IMPLEMENTED IN UZBEKISTAN - F.E. Toshboyev; D.D. Yuldosheva (Web of Journals Publishing, 2025)
This article analyzes the negative consequences of the policy of collectivization of agriculture carried out by the Soviet government in Uzbekistan. Based on historical documents, archival materials and modern research, the social instability, hunger and poverty that have arisen as a result of this policy are considered.
Keywords: October Revolution, land and water reform, Bolsheviks, collectivization, Grandfather Rahman